2016
DOI: 10.1088/1752-7155/10/1/017102
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled and non-exhaled non-invasive markers for assessment of respiratory inflammation in patients with stable COPD and healthy smokers

Abstract: We aimed at comparing exhaled and non-exhaled non-invasive markers of respiratory inflammation in patients with COPD and healthy subjects and define their relationships with smoking habit. Forty-eight patients with stable COPD who were ex-smokers, 17 patients with stable COPD who were current smokers, 12 healthy current smokers and 12 healthy ex-smokers were included in a cross-sectional, observational study. Biochemical [prostaglandin (PG) E 2 , 15-F 2t -isoprostane, fraction of exhaled nitric oxide (F E NO)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 29 publications
(74 reference statements)
0
24
0
2
Order By: Relevance
“…In a breathomics multidimensional approach to assessment of drugs for COPD, we show anti-inflammatory effects of an extrafine beclomethasone/formoterol FDC pMDI vs. formoterol alone as reflected by reduced levels of sputum PGE 2 , a potent inflammatory mediator in the airways (Clarke et al, 2005; Holden et al, 2010), and EBC acetate which were found elevated in COPD patients (De Laurentiis et al, 2008, 2013; Airoldi et al, 2016; Santini et al, 2016). …”
Section: Discussionmentioning
confidence: 93%
“…In a breathomics multidimensional approach to assessment of drugs for COPD, we show anti-inflammatory effects of an extrafine beclomethasone/formoterol FDC pMDI vs. formoterol alone as reflected by reduced levels of sputum PGE 2 , a potent inflammatory mediator in the airways (Clarke et al, 2005; Holden et al, 2010), and EBC acetate which were found elevated in COPD patients (De Laurentiis et al, 2008, 2013; Airoldi et al, 2016; Santini et al, 2016). …”
Section: Discussionmentioning
confidence: 93%
“…The sample size across studies varied from 21 to 212, with a total number of 1,669. The majority of studies were from Europe,1012,15,18–20,22,23,26–30,33 with 1 study from Australia,17 1 study from America,13 2 studies from Africa,21,32 and 5 studies from Asia 14,16,24,25,31. In terms of diagnosis of COPD, 9 studies used doctor-diagnosis,13,15,17,21,23,29,31,32 8 studies used GOLD guideline,10,12,14,18,22,24,26,30,33 2 applied American Thoracic Society criteria,11,16 2 applied European Respiratory Society criteria,20,27 2 applied British Thoracic Society guidelines,19,28 and 1 applied Chinese Medical Association guidelines 25…”
Section: Resultsmentioning
confidence: 99%
“…Cigarette smoking is another potential confounding factor in FeNO measurements, with smoking COPD patients having lower FeNO than non‐smoking patients . We did not evaluate whether the findings differed between smokers and non‐smokers.…”
Section: Discussionmentioning
confidence: 99%